1996
DOI: 10.1103/physrevb.54.3200
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of atomic structure, electronic structure, and the electronic transport mechanism in amorphous Al-Cu-Y and Mg-Cu-Y ternary alloys

Abstract: The local atomic structure in the amorphous Al x ͑Cu 0.4 Y 0.6 ͒ 100Ϫx and Mg x ͑Cu 0.4 Y 0.6 ͒ 100Ϫx ͑0рxр85͒ alloys was determined by neutron-diffraction experiments. The electronic structure near the Fermi level was determined using the same samples by means of x-ray photoemission spectroscopy and soft x-ray spectroscopy. Both sets of data are combined to determine self-consistently and uniquely the local atomic structure in both Al-and Mg-based amorphous alloys. The bonding nature and resulting atomic envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 12 publications
(20 reference statements)
3
20
0
Order By: Relevance
“…In this case, the CSRO modeling suggests that the atomic structure will be tending towards a solvent-solute type topology, as Y (solvent) has a negative CSRO with both solutes. This tendency matches that seen in the experimental results as the solute-solute clustering has disappeared, and Y clustering around solute atoms, especially Cu, has begun to develop, as seen in the Mg 30 Cu 26 Y 42 illustration [14].…”
Section: Chemical Short-range Ordersupporting
confidence: 85%
See 2 more Smart Citations
“…In this case, the CSRO modeling suggests that the atomic structure will be tending towards a solvent-solute type topology, as Y (solvent) has a negative CSRO with both solutes. This tendency matches that seen in the experimental results as the solute-solute clustering has disappeared, and Y clustering around solute atoms, especially Cu, has begun to develop, as seen in the Mg 30 Cu 26 Y 42 illustration [14].…”
Section: Chemical Short-range Ordersupporting
confidence: 85%
“…The reported radial distribution function [14] of amorphous Mg 80 Cu 8 Y 12 indicated primarily Mg-Mg and Cu-Y correlations. It was concluded experimentally that in the Mg 80 Cu 6 Y 12 alloy, the amorphous structure consisted of Cu-Y clusters surrounded by a randomly distributed Mg matrix, as the CSRO predicts.…”
Section: Chemical Short-range Ordermentioning
confidence: 94%
See 1 more Smart Citation
“…For example, Inoue et al have prepared a series of Al-Cu-Y metallic glasses within the composition range of 3-22 at% Y by melt spinning and found that when the Al content is more than 80 at%, the metallic glasses have good bend ductility [20,21]. Fukunaga et al, have obtained Alx(Cu0.4Y0.6)100−x (x = 0, 5, 10, 15, 20, 30, 80, and 85) metallic glasses by arc melting and further studied their atomic and electronic structures [31]. In addition, Idzikowski et al have obtained fully amorphous Al8Cu42Y50 ribbon by melt-spinning and further tracked its structural evolution with varying annealing time [32].…”
Section: Resultsmentioning
confidence: 99%
“…To further validate the predicted GFR of the Al-Cu-Y system, the experimental identified glass formation compositions reported so far in the literature are extensively collected [20,21,[30][31][32][33] and marked by the red dots in Figure 1. For example, Inoue et al have prepared a series of Al-Cu-Y metallic glasses within the composition range of 3-22 at% Y by melt spinning and found that when the Al content is more than 80 at%, the metallic glasses have good bend ductility [20,21].…”
Section: Resultsmentioning
confidence: 99%